Pengaruh kompensasi, motivasi kerja, dan lingkungan kerja terhadap kinerja karyawan PT. Atika jaya perkasa, pandean, Kab. Umbulharjo, Yogyakarta - Riadi, Wiwit Enggal; Subarjo, Subarjo (Peneliti.net, 2023)
This study aims to analyze the effect of Compensation, Work Motivation, and Work Environment on the Performance of PT. Atika Jaya Perkasa Pandean, Umbulharjo District, Yogyakarta. This study uses the independent variables Compensation (X1), Work Motivation (X2), and Work Environment (X3), and Employee Performance (Y) as the dependent variables. In this study, the population and sample were all active employees of PT. Atika Jaya Perkasa Pandean numbering 100 people This research is included in quantitative research because the approach used for research proposals, processes, hypotheses, data analysis, data conclusions to writing uses aspects of measurement, calculation, formula and certainty of numerical data. The analysis data uses a multiple linear regression formula. The results showed that: (1) Compensation has a significant effect on employee performance on employee performance, (2) Motivation does not have a significant effect on employee performance, (3) Work Environment has a positive and significant effect on employee performance, (4) Compensation, Motivation and Work Environment have a partial or simultaneous effect on Employee Performance. This result is shown by the significance value of the Compensation variable to the Employee Performance variable of 0.009, the Motivation variable to Employee Performance of 0.675, the Work Environment variable to Employee Performance of 0.000, and the significance of the Compensation, Motivation, and Work Environment variables to Employee Performance of 0.000. From the results of this study, it can be concluded that Compensation, Work Motivation, and Work Environment have an influence and significance on Employee Performance.